Dea sebagai analisis alternatif dalam penelitian akuntansi - Aritonang, Lerbin R (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2006)
Efficiency is an important concept in accounting. Analyzing efficiency can be done by some analyses. One of them is data envelopment analysis (DEA). This article describes how to use DEA and what the limitations, advantages and assumptions are. Some applications of DEA are also presented, so that readers have better knowledge of DEA.